Do Nonresidential Fathers’ Financial Support and Contact Improve Children’s Health? - Hofferth, Sandra L. (2011)
Nonresidential father investment of time and money has been shown to ameliorate the negative consequences of family dissolution on children’s behavior and achievement; however, no research has shown whether this investment also has positive effects on child health. Using data from the Early Childhood Longitudinal Survey, Kindergarten cohort, this research uses a two-wave cross-lagged model to examine how child support and contact are associated with maternal reports of children’s physical health over time following parental separation. Child support in kindergarten is not associated with child health in third grade. Instead, children who are healthier in kindergarten receive greater financial support from their father. Although contact and child support are positively related, greater contact is not associated with better child health.